Copper-aluminum hydrotalcite modified zinc negative electrode and preparation method and application thereof

By synthesizing copper-aluminum hydrotalcite materials, the interface properties of zinc negative electrodes are optimized, and the problems of safety and resource limitations of lithium-ion batteries are solved, and the structural stability and cycle life of aqueous zinc-ion batteries are significantly improved, thus reducing the risk of dendrites. It also inhibits hydrogen evolution reaction and corrosion on the zinc surface, improving the safety and performance of the battery.

CN119133355AInactive Publication Date: 2024-12-13CHINA UNIV OF PETROLEUM (EAST CHINA) +1

Patent Information

Application Number
CN202411317832.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lithium-ion batteries have problems with safety, resource limitations and environmental impacts, and water-based zinc-ion batteries are prone to short circuits and failure risks caused by dendrite growth during charging and discharging, which affects the safety and cycle life of the battery.

Method used

By synthesizing copper-aluminum hydrotalcite materials, the interface properties between the electrolyte and the negative electrode are optimized, and a nano-scale sheet structure is used to regulate the deposition process of zinc ions, prevent dendrites from growing, and improve the structural stability of the battery.

Benefits of technology

It significantly enhances the structural stability of zinc negative electrode, reduces the risk of battery short circuit and failure caused by dendrite growth, improves the safety and cycle life of the battery, and inhibits hydrogen evolution reaction and corrosion on the zinc surface, improves the performance of the battery and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133355A_ABST
    Figure CN119133355A_ABST
Patent Text Reader

Abstract

The invention provides a copper-aluminum hydrotalcite modified zinc negative electrode and a preparation method and application thereof, and belongs to the technical field of electrodes. The preparation method comprises the following steps: S1, adding copper salt and aluminum salt into water, stirring and dissolving, adding alkali liquor, stirring and reacting, centrifugally washing, crystallizing and drying to obtain copper-aluminum hydrotalcite; and S2, adding the copper-aluminum hydrotalcite into a binder for continuous grinding, then adding N-methyl pyrrolidone for grinding and mixing, paving a zinc foil, removing a surface oxide layer, uniformly coating the zinc foil with the copper-aluminum hydrotalcite slurry by using a coater, drying, and cutting to obtain the electrode plate. The interface property between the electrolyte and the negative electrode is optimized by synthesizing the copper-aluminum hydrotalcite material, the deposition process of zinc ions is effectively regulated and controlled, deposition of the zinc ions on the surface of the negative electrode is more uniform and stable, the dendritic crystal growth problem possibly occurring in the charging and discharging process of the zinc negative electrode is effectively prevented, and the service life of the zinc negative electrode is prolonged. Battery short circuit and failure risks caused by dendritic crystal growth are reduced, so that the safety and the cycle life of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrodes, and in particular to a copper-aluminum hydrotalcite-modified zinc negative electrode and a preparation method and application thereof. Background Art

[0002] Electrochemical energy storage is a kind of energy storage technology that stores electrical energy through chemical batteries and discharges it when needed. Compared with other energy storage technologies, it has the advantages of large energy capacity and fast response. With the rapid development of the new energy industry, electrochemical energy storage technology has a very promising prospect. Among them, lithium-ion batteries are widely used in various electronic products in life. They have the advantages of low mass, low potential, high energy density and high cycle stability. However, lithium-ion batteries also have many problems. The first is the safety issue. Lithium-ion batteries may cause overheating, short circuit or even explosion under the conditions of excessive charging and discharging, high temperature or external damage; the second is resource limitations. The main raw materials of lithium-ion batteries are rare metals such as lithium and cobalt, which are limited in supply and costly; finally, environmental impact and sustainability. The mining and refining of lithium-ion battery materials, the recycling and treatment of waste batteries, and the toxicity of organic electrolytes may have a certain impact on the environment. In addition, lead-acid batteries also need to develop new batteries due to the emission of pollutants, low life and energy density during use.

[0003] Aqueous batteries have a high research prospect. Aqueous batteries use aqueous electrolytes instead of organic electrolytes, which greatly improves the safety performance of the battery. In addition, water molecules are non-toxic and non-volatile, so water solvents that are more environmentally friendly are used. At present, the known developed aqueous metal ion batteries include zinc ion batteries, sodium ion batteries, lithium ion batteries, potassium ion batteries, aluminum ion batteries, magnesium ion batteries and calcium ion batteries.

[0004] Zinc metal in aqueous zinc ion batteries has advantages in safety, stability and theoretical capacity. Compared with other metals, zinc metal has a higher redox potential and can be directly used as the negative electrode material of aqueous batteries. Based on the above advantages, aqueous zinc ion batteries (AZIBs) show great application prospects. Summary of the invention

[0005] The purpose of the present invention is to propose a copper-aluminum hydrotalcite modified zinc negative electrode and its preparation method and application. The interface properties between the electrolyte and the negative electrode are optimized by synthesizing the copper-aluminum hydrotalcite material. The nano-scale sheet structure of the copper-aluminum hydrotalcite can significantly enhance the structural stability of the zinc negative electrode, effectively regulate the deposition process of zinc ions, make the deposition of zinc ions on the negative electrode surface more uniform and stable, effectively prevent the dendrite growth problem that may occur in the zinc negative electrode during the charge and discharge process, reduce the risk of battery short circuit and failure caused by dendrite growth, thereby improving the safety and cycle life of the battery. .

[0006] The technical solution of the present invention is achieved in this way: The present invention provides a method for preparing a copper-aluminum hydrotalcite-modified zinc negative electrode, comprising the following steps: S1. Synthesis of copper-aluminum hydrotalcite: copper salt and aluminum salt were added to water and stirred to dissolve, alkali solution was added, stirred to react, a blue suspension was obtained, centrifuged, washed, crystallized, and dried to obtain copper-aluminum hydrotalcite; S2. Preparation of electrode: Add copper-aluminum hydrotalcite to a binder and continue grinding, then add a solvent and mix well. Flatten the zinc foil and remove the surface oxide layer. Then evenly apply the copper-aluminum hydrotalcite slurry on the zinc foil, dry it, and cut it to obtain an electrode sheet.

[0007] As a further improvement of the present invention, the copper salt is selected from at least one of copper chloride, copper nitrate and copper sulfate.

[0008] As a further improvement of the present invention, the aluminum salt is selected from at least one of aluminum copper chloride, aluminum nitrate, and aluminum sulfate.

[0009] As a further improvement of the present invention, the alkali solution is a 0.05-2 mol / L NaOH or KOH solution.

[0010] As a further improvement of the present invention, the molar ratio of the copper salt to the aluminum salt is (18-24): (1-12).

[0011] As a further improvement of the present invention, the temperature of the crystallization reaction is 80-150° C. and the time is 15-25 hours.

[0012] As a further improvement of the present invention, the binder is one of PVDF, PTFE and CMC.

[0013] As a further improvement of the present invention, the mass ratio of the copper-aluminum hydrotalcite, the binder and the N-methylpyrrolidone is 10:2-7:1-5.

[0014] The present invention further protects a copper-aluminum hydrotalcite-modified zinc negative electrode prepared by the above preparation method.

[0015] The present invention further protects the use of the copper-aluminum hydrotalcite-modified zinc negative electrode in the preparation of energy storage batteries.

[0016] The present invention has the following beneficial effects: the present invention optimizes the interface properties between the electrolyte and the negative electrode by synthesizing the copper-aluminum hydrotalcite material, and the nano-scale sheet structure of the copper-aluminum hydrotalcite can significantly enhance the structural stability of the zinc negative electrode, effectively regulate the deposition process of zinc ions, make the deposition of zinc ions on the surface of the negative electrode more uniform and stable, effectively prevent the dendrite growth problem that may occur in the zinc negative electrode during the charge and discharge process, reduce the risk of battery short circuit and failure caused by dendrite growth, thereby improving the safety and cycle life of the battery. In addition, the hydrogen evolution reaction and the corrosion of the zinc surface can also be suppressed. The hydrogen evolution reaction consumes the water in the electrolyte and causes the increase of the internal pressure of the battery. The corrosion of the zinc surface will further reduce the effective surface area of ​​the negative electrode and increase the internal resistance, thereby affecting the capacity and efficiency of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0018] Figure 1 is the XRD pattern of CAL with different metal ratios; Figure 2 XRD patterns of bare Zn (Bare-Zn) and copper-aluminum hydrotalcite-modified zinc electrode (Cu-Al LDH@Zn) are compared; Figure 3 The SEM images of the products, where a and b are images of copper-aluminum hydrotalcite, c is an image of bare Zn, and d is an image of copper-aluminum hydrotalcite-modified zinc negative electrode; Figure 4 The contact angles of bare Zn (Bare Zn) and copper-aluminum hydrotalcite-modified zinc anode (Cu-Al LDH@Zn) in 2 M ZnSO4 electrolyte. Figure 5 The electrochemical performance diagram of the symmetric battery at 1 mA cm-2 and 1 mA h cm-2; Figure 6 The electrochemical performance diagram of the symmetric battery at 10 mA cm-2 and 2 mA h cm-2; Figure 7 For a symmetrical cell at 1 mA cm -2 Rate performance diagram under 2 conditions. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 1. Synthesis of copper-aluminum hydrotalcite Weigh CuSO4 and Al2(SO4)3 in a certain proportion, add 15 mL of water and stir for 15 min, add 40 mL of 0.25 mol / L NaOH solution, stir for 2 h to obtain a blue suspension, centrifuge and wash, crystallize at 110℃ for 20 h, and dry to obtain copper-aluminum hydrotalcite, named "Cu-Al LDH". During the synthesis process, the molar ratio of metallic copper and aluminum was controlled to be 20:7, and the prepared copper-aluminum hydrotalcites were named "CA-20-7".

[0021] 2. Preparation of electrodes 10g of the prepared copper-aluminum hydrotalcite and 5g of the binder polyvinylidene fluoride (PVDF) were mixed and ground, and then 4g of N-methylpyrrolidone (NMP) was fully ground and mixed. After the zinc foil was flattened and the surface oxide layer was removed, the copper-aluminum hydrotalcite slurry was evenly coated on the zinc foil using an applicator, dried at 50°C, clamped up and down with weighing paper, and placed on a manual slicer to cut into electrode sheets with a diameter of 10 mm, named "Cu-Al LDH@Zn", and the uncoated pure zinc foil was named "Bare Zn".

[0022] 3. Assembly of symmetrical batteries According to the order of positive electrode shell, positive electrode, diaphragm, negative electrode, gasket, spring sheet and negative electrode shell, they are assembled into a symmetrical battery. Among them, the working electrode (positive and negative electrode) uses two identical electrode sheets, the diaphragm is a GF / D type glass fiber diaphragm, and the electrolyte is a 2 M ZnSO4 solution. The battery is placed on a button battery sealing machine, and the pressure is adjusted to maintain for 20 s before taking it out.

[0023] Example 2 Compared with Example 1, the difference is that during the synthesis process, the molar ratio of metallic copper to aluminum is controlled to be 20:9, and the prepared copper and aluminum hydrotalcites are named "CA-20-9" respectively.

[0024] Example 3 Compared with Example 1, the difference is that during the synthesis process, the molar ratio of metallic copper to aluminum is controlled to be 20:10, and the prepared copper and aluminum hydrotalcites are named "CA-20-10" respectively.

[0025] Example 4 Compared with Example 1, the difference is that during the synthesis process, the molar ratio of metallic copper to aluminum is controlled to be 20:12, and the prepared copper and aluminum hydrotalcites are named "CA-20-12" respectively.

[0026] Example 5 Compared with Example 1, the difference is that during the synthesis process, the molar ratio of metallic copper to aluminum is controlled to be 18:10, and the prepared copper and aluminum hydrotalcites are named "CA-18-10" respectively.

[0027] Test Example 1 Test Example 1 Structural Characterization 1. X-ray diffraction analysis X-ray diffraction analysis (XRD) can be used to characterize the crystal structure of solid materials. The peaks of the diffraction spectrum can be compared with the JCPDS card to obtain the structural composition of the corresponding material. The XRD diffractometer used in the present invention has an emission source of Cu Kα, λ of 1.5406 Å, a current of 40 mA, a voltage of 40 kV, a step time of 0.25 s, and a step length of 0.02 o , the test range is 5 o ~80 o The test was carried out under the conditions of

[0028] Figure 1 For different n(Cu 2+ ):n(Al 3+ ) synthesized copper aluminum hydrotalcite XRD spectrum. It can be seen from the figure that when n(Cu 2 + ):n(Al 3+ )=18:10, 20:12, 20:10, 20:9 and 20:7, at 2θ=10.58 o , 21.02 o and 35.77 o Three unique diffraction peaks of copper-aluminum hydrotalcite appeared, corresponding to the (003), (006) and (012) crystal planes of copper-aluminum hydrotalcite (37-0630), indicating that copper-aluminum hydrotalcite was successfully synthesized. 2+ ):n(Al 3+ ) ratio decreases, the impurity peaks of copper-aluminum hydrotalcite also decrease. 2+ ):n(Al 3+ )=20:7, the impurity peaks of copper-aluminum hydrotalcite are the least, indicating that the copper-aluminum hydrotalcite synthesized under this condition has higher purity.

[0029] The synthesized copper-aluminum hydrotalcite was characterized by XRD before and after coating. Figure 2 As shown, the electrode sheet after coating has a 2θ of 10.39 o and 20.92 o The diffraction peak of hydrotalcite appeared at the surface, and it also had the characteristic diffraction peak of bare zinc, indicating that the copper-aluminum hydrotalcite has been successfully coated on the surface of the zinc negative electrode.

[0030] 2. Scanning electron microscopy analysis Scanning Electron Microscopy (SEM) is a unique means of observation. Its working principle is to scan the sample by focusing an extremely fine and high-energy electron beam. When this beam of high-energy electrons interacts with the sample material, various physical information will be stimulated. Subsequently, these stimulated physical information will be collected, amplified, and ultimately converted into visual images, thereby achieving detailed observation and characterization of the microscopic morphology of the material. In the present invention, the surface morphology of the copper-aluminum hydrotalcite and the zinc negative electrode before and after coating is mainly characterized to obtain SEM images. The surface morphology of the copper-aluminum hydrotalcite is analyzed by SEM, such as Figure 3 (a) It can be seen that Cu-Al LDH has an obvious lamellar hexagonal structure, the lamellar layers are tightly stacked, and the particle size is uniform, which is in line with the typical characteristics of hydrotalcite. Figure 3 (b) and (c) are SEM images of the zinc negative electrode surface before and after coating. It can be seen from the figure that the surface of the zinc negative electrode is not completely smooth, and there are obvious cracks, protrusions and scratches, which are not conducive to the uniform deposition of zinc ions, resulting in a tip effect, which leads to a short circuit of the battery and affects the battery cycle life. The surface of the zinc negative electrode after coating is relatively flat, forming a uniform and dense coating with a typical layered structure, proving that the copper-aluminum hydrotalcite is successfully coated on the zinc negative electrode.

[0031] 3. Contact angle analysis The contact angle is tested by a contact angle tester, and its size directly reflects the wettability of the electrode to the electrolyte before and after the construction of the interface modification layer. In this experiment, 2 M ZnSO4 was added as the electrolyte to the zinc negative electrode without the construction of the interface modification layer and after the construction of the copper-aluminum hydrotalcite interface modification layer. It was left to stand for 5 s, and photos were taken and the data was recorded. In order to ensure the accuracy of the data, 5 different sites were selected for testing in each group of samples, and the average value of the data was calculated. The smaller the contact angle, the better the wettability of the electrode surface, which means that the electrolyte has a faster diffusion rate on the electrode surface. The wettability of the electrolyte to Bare Zn and Cu-Al LDH@Zn electrodes was analyzed by contact angle test, such as Figure 4It can be seen that the contact angle between Cu-Al LDH@Zn and the electrolyte is 55.2°, while the contact angle between Bare Zn and the electrolyte is 95.7°. The contact angle of Cu-Al LDH@Zn is significantly smaller than that of Bare Zn, indicating that the copper-aluminum hydrotalcite interface modification layer can improve the wettability of the electrode to the electrolyte, thereby facilitating the adsorption of dehydrated Zn. 2+ , promoting [Zn(H2O)6] 2+ Migration from the bulk electrolyte to the Zn anode surface reduces the interfacial electron transfer impedance and promotes uniform electrodeposition.

[0032] Test Example 4 Cyclic Stability Test Battery cycle stability test is a key technology for evaluating battery performance and life. The cycle stability of the battery is evaluated by repeatedly performing charge and discharge cycles. The reversibility of the battery during the charge and discharge process is evaluated by observing the shape of the battery's charge and discharge curve and the changes during the cycle. At the same time, the cycle stability test also has the important function of detecting battery safety. Constant current charge and discharge tests were performed on bare Zn and Cu-Al LDH@Zn symmetric batteries, such as Figure 5 As shown in the figure, after about 96 hours of cycling, the bare zinc symmetric battery suddenly short-circuited due to zinc dendrites piercing the separator, and the direct contact between the positive and negative electrodes caused the battery to decrease in polarization potential. In contrast, the symmetric battery Cu-Al LDH@Zn exhibited an ultra-stable cycle life (duration > 2260 hours). Figure 6 As shown, at 10 mA cm -2 At ultra-high current density, thanks to the regulation of the Cu-Al LDH interface layer, the symmetrical battery can maintain stable cycling for more than 834 h without obvious polarization fluctuations. However, the symmetrical device assembled with pure zinc electrodes showed severe polarization at the beginning of the cycle, and the symmetrical battery short-circuited and failed after only 82 h of cycling. Figure 7 It can be seen that the Cu-Al LDH@Zn symmetric battery has high reversibility and cycle stability.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-aluminum hydrotalcite-modified zinc negative electrode, characterized in that: The following steps are involved: S1. Synthesis of copper-aluminum hydrotalcite: copper salt and aluminum salt were added to water and stirred to dissolve, alkali solution was added, stirred to react, a blue suspension was obtained, centrifuged, washed, crystallized, and dried to obtain copper-aluminum hydrotalcite; S2. Preparation of electrode: Add copper-aluminum hydrotalcite to a binder and continue grinding, then add a solvent and mix well. Flatten the zinc foil and remove the surface oxide layer. Then evenly apply the copper-aluminum hydrotalcite slurry on the zinc foil, dry it, and cut it to obtain an electrode sheet.

2. The preparation method according to claim 1, characterized in that: The copper salt is selected from at least one of copper chloride, copper nitrate and copper sulfate.

3. The preparation method according to claim 1, characterized in that: The aluminum salt is selected from at least one of aluminum copper chloride, aluminum nitrate, and aluminum sulfate.

4. The preparation method according to claim 1, characterized in that: The alkali solution is 0.05-2 mol / L NaOH or KOH solution.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the copper salt to the aluminum salt is (18-24): (1-12).

6. The preparation method according to claim 1, characterized in that: The temperature of the crystallization reaction is 80-150° C. and the time is 15-25 hours.

7. The preparation method according to claim 1, characterized in that: The binder is one of PVDF, PTFE and CMC.

8. The preparation method according to claim 1, characterized in that: The mass ratio of the copper-aluminum hydrotalcite, the binder and N-methylpyrrolidone is 10:2-7:1-5.

9. A copper-aluminum hydrotalcite-modified zinc negative electrode prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the copper-aluminum hydrotalcite-modified zinc negative electrode as claimed in claim 9 in preparing energy storage batteries.

Citation Information

Patent Citations

  • Application of zinc-based ternary layered composite oxide to zinc-nickel battery electrode material

    CN103579588A

  • Zinc-aluminium hydrotalcite rich in cuprous ions and preparation method and application of zinc-aluminium hydrotalcite

    CN110372030A

  • Zinc negative electrode with zinc ion conductivity interface modification layer, battery and preparation method

    CN111933912A

  • ZnO (at) ZnS (at) C composite negative electrode material for zinc-nickel secondary battery as well as preparation method and application of ZnO (at) ZnS (at) C composite negative electrode material

    CN116425189A

  • Mixture for zinc electrode

    JP2015197976A

Cited By

  • Preparation method of modified hydrotalcite modified zinc negative electrode

    CN120545300A